Counseling and Demonstration of Supplementary Feeding for Toddlers as an Effort to Prevent Stunting in Randegansari Village - Rohmawati, Riska; Dwi Angelia, Tariza; Prianto, Alfi Putri; Ashfiatin Nada; Lestari, Eka Harum (UNUSA Press, 2024)
Stunting is a disorder that occurs due to the accumulation of bad nutrition. Stunting carries a risk of causing pain, slowing motor development and can even cause death. Since the last 10 years, people around the world have seen Moringa as a tropical plant that is easy to cultivate because it can be used in all types of soil and does not need intensive care. Service activities are one of the efforts made by tertiary institutions through the KKN-T (Thematic Real Work Lecture) program which aims to educate the public about stunting knowledge. This community service activity is one of the KKN-T work programs (Thematic Real Work Lectures) which was held at the Tlapak Hamlet Posyandu, Randegansari Village, on Tuesday, August 1, 2023 at 08.00 WIB. In improving human quality, it must start early, namely from infancy. In order to realize and build quality human resources, many of the mothers have implemented and practiced the activities of how to make PMT.